Assessment of skeletal muscle microcirculation in type 2 diabetes mellitus using dynamic contrast-enhanced ultrasound: A pilot study. (September 2013) - Amarteifio, Erick; Wormsbecher, Stephanie; Demirel, Serdar; Krix, Martin; Braun, Simone; Rehnitz, Christoph; Delorme, Stefan; Kauczor, Hans-Ulrich; Weber, Marc-André
Purpose: To investigate muscular micro-perfusion by employing dynamic contrast-enhanced ultrasound (CEUS) and performing transient arterial occlusion in patients with type 2 diabetes mellitus (DM-2). Methods: Twenty DM-2 patients (mean age, 58 ± 8.6 years; duration of diabetes, 15.4 ± 12.1 years) and 20 healthy volunteers (mean age, 54 ± 5.4 years) participated. CEUS was applied to the calf, while 4.8 mL of SonoVue ® was injected intravenously. At the thigh level, arterial occlusion (60 s) was performed. CEUS parameters (tmax, max, AUCpost and m) were evaluated and Pearson-product-moment correlation coefficients were computed. Results: A moderate negative correlation of HbA1c and max was established (−0.53). Max in patients with DM-2 >10 years was 79.89 ± 37.4. Max in patients with DM-2 duration <10 years was 137.62 ± 71.72 (p = 0.04). AUCpost in patients with DM-2 duration >10 years was 3924.01 ± 1630.52. AUCpost in patients with DM-2 duration <10 years was 6453.59 ± 3206.23 (p = 0.04). Conclusion: Patients with long history of DM-2 present with impaired muscular perfusion. CEUS and transient arterial occlusion may provide appropriate methods for semi-quantitative evaluation of muscular micro-perfusion in patients with DM-2.